Evaluación genotóxica del agua del Río Grande (Antioquia, Colombia) mediante frecuencia de eritrocitos micronucleados de Brycon henni (Characiformes : Characidae) (2017)
ABSTRACT: The permanent monoculture of bananas and plantains farming in the middle of Río Grande (Turbo - Antioquia) requires the application of a variety of pesticides. Inappropriate banana production practices in this region, have often led to waterbody pollution by agrochemicals from leachate and runoff processes. Currently, fish are the most common vertebrates used as bioindicators of water quality, because they are very sensitive to the presence of contaminants. Our main goal with this study was to compare the frequency of micronucleated erythrocytes (MNE) in peripheral blood specimens of fish Brycon henni, from two locations (polluted and unpolluted) in the Rio Grande. We evaluated the frequency of MNE in peripheral blood samples of fish B. henni from each location during two rainy seasons in 2010 and two dry seasons in 2011. Blood samples were collected, fixed for 24 h, and then were stained with Giemsa. Among results, we found that the median frequency of MNE was higher in the polluted site by agrochemical discharges (0.15±0.18), than in the unimpacted site (0.06±0.08). Furthermore, the frequency of MNE in B. henni during the dry season was highly significant for both locations. The results of this study indicated that the analysis of MNE in B. henni could be recommended as a suitable method for in situ detection of environmental genotoxins.